Variation in the use and interpretation of null subjects: A view from Greek and Italian. Issue 1 (18th September 2020) - Torregrossa, Jacopo; Andreou, Maria; Bongartz, Christiane M.
Abstract : We aim to understand whether Greek and Italian, two null subject languages, differ in the use and interpretation of null subjects, based on evidence from both a production and a comprehension experiment. The results of the two experiments show that the two languages differ in the extent to which they comply with the Position of Antecedent Strategy as formulated by Carminati (2002 ). In order to account for this difference, we introduce a principle which defines prominence of sentence constituents in terms of hierarchical height, elaborating on a recent proposal by Rizzi (2018 ). Then we show that the prominence of subject and object constituents in Greek and Italian reflects word-order differences between the two languages (Roussou & Tsimpli 2006 ). In more general terms, this paper argues in favour of a multi-factorial approach to reference interpretation, in that syntactic factors interact with discourse factors, leading to a gradient variety of reference possibilities.